Rancang Bangun Sistem Monitoring dan Kontrol Otomatis Water Level pada Tangki Cascade di Mv Prima Andalan 1 - Bima Purmasheka; Antonius Edy Kristiono; Akhmad Kasan Gupron (Pusat Riset dan Inovasi Nasional, 2024)
From this research, monitoring can be carried out using the XH-M203 water level which can run a wireless sensor to measure the water in the tank and then the results of these measurements will give a command to the pump to fill the tank. This tool is made to automatically control the height and automatically fill the tank. The design of this tool is based on the fact that some ships still use a manual system in the form of a float gauge to monitor water levels, so by designing this tool the monitoring and control process will be easier. System testing shows that the system is able to control water levels with high accuracy and is responsive to changes in water levels. The results of this research are that the XH-M203 water level is able to detect height and automatically control the simulated tank. The results of the detection are processed through a controller and LED as a marker for high and low levels so that all parties can know the water level in the tank. Then automatic control uses a pump which will fill automatically so that the tank capacity can be controlled through this tool. With 6 trials of 90% capacity in calm water there was an error of 0.01% and 90% capacity with the tank shaking there was an error of 0.01%. The next test with a tank capacity of 60% in still water conditions has an error of 0% and a capacity of 60% there is vibration there is a 0% error, and testing with a tank capacity of 30% in still water conditions there is an error of 0% and at 30% capacity there is vibration in the tank there is an error of 0 %. So this tool can work with an accuracy of 99.98% and a tool error of 0.02%.